The role of television shows in mitigating climate change in Kenya - Nkanatha, John (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
The media plays a pivotal role of informing, educating and entertaining viewers. This informative role involves the use of computing and informatics technologies to disseminate information to the masses. Governments and their citizens depend on the mass media to disseminate information and set agenda for development and other activities. Electronic media such as television form part of the mass media that wield the power to set and build agenda for climate adaptation and resilience. This paper explores the role and effectiveness of television in mitigating climate change through television news and other programmes coverage, aimed at informing the masses on the effects of climate change. The objective of this study was to trace the role and effectiveness of television in conveying information on green energy utilization and pollution mitigation. A purposive sampling was done to select TV shows airing agriculture/climate change content. Guided by the amassed literature and on-line survey, a case study research design of different Kenyan television shows was studied using thematic content analysis. The paper relied on secondary data gleaned from library research, internet sources and data published on the pertinent issue. The results show that television has a significant role to play on viewers’ knowledge on the issue of climate change. However, Kenyan television has not lived to this reputation. In Kenyan newsrooms stories on climate change and environmental degradation are relegated to the background as they compete with political, health and economic matters in news that attract more public attention. The recommendations enumerate the mitigating roles that the media can play in efforts to curb global warming and the attendant climate change. There is need to give prominence to stories on matters environment. Global warming has led to depletion of natural resources and burning of fossil fuels has become a threat to the environment. This threat can be mitigated through well packaged and delivered messages using the media which is a powerful tool for disseminating information and diffusion of innovations and ideas.